GAMBARAN POLA KONSUMSI BUAH DI RUMAH TANGGA KOTA PALEMBANG - Marsita, Tita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Fruit in South Sumaterais mostlytropical fruit whichis relatively seasonal. However, the fruits in Palembangcityis available throughout the year. If it associated withthe levelofconsumption, availabilityoffruit does not directly guarantee that the community can fulfill all of its consumption.Therefore, the pattern of consumption of fruitvaries depending on consumption patterns based on household characteristics. This research aims to describe the consumption pattern of household fruits in Palembang City. The data used are cross section data, primary data is from food consumption expenditure modules for fruit groups household of the National Social Economic Survey in2017 Statistical officeof Palembang City. Data of783 householdsare used for the purpose of this research and analysed using is a descriptive method with tabulation.The results of the study revealed that fruit consensus patterns based on low and medium income groups were dominated by bananas (31.9% and 23%) and high groups of oranges(23.2%), then based on the number of household members consuming fruit in the number of members large and medium households are dominated by bananas (24.6% and 22.5%), and small households in oranges(22.4%). Based on the education level housewives withlow educationlevel mostly consumebananas (24.3%), moderate and high education levels of consumeoranges(23.3% and 22.9%respectively).So, it can be concluded that, the dominant fruit share based on the socio-economic characteristics is bananas.